Nawiedzony dom i widma faszyzmu: o "Tell Me I’m Worthless" Alison Rumfitt - Herman, Anouk (Zagadnienia Rodzajów Literackich, 2025)
This article explores the motif of the haunted house in Alison Rumfitt’s Tell Me I’m Worthless and situates the novel among other works that employ the same trope, including Shirley Jackson’s The Haunting of Hill House and Daphne du Maurier’s Rebecca. Rumfitt uses the haunted house to address the resurgence of fascism — an especially relevant context given the Brexit era in which the novel was written — and the ways in which it oppresses women and marginalized groups. The political dimension of the haunted house motif is conveyed not only through the connection between the demonic mansion and fascism, but also through the class aspect of grand aristocratic villas, where corruption and hatred toward the lower classes begin to take the form of hauntings. This article examines the political dimensions of the haunted house motif, arguing that its significance extends beyond Tell Me I’m Worthless to other narratives as well. Rumfitt’s novel has been interpreted, among other things, in the context of Mary Russo’s concept of the female grotesque and Barbara Creed’s notion of female monstrosity. Additionally, the article situates Rumfitt’s novel within Mark Fisher’s concept of hauntology, positioning its haunted house within what the author of The Weird and the Eerie defines as the eerie.